Predicting Prognosis and Distinguishing Cold and Hot Tumors in Bladder Urothelial Carcinoma Based on Necroptosis-Associated lncRNAs - Liu, Dongze; Xu, Shengxian; Chang, Taihao; Ma, Shenfei; Wang, Kaibin; Sun, Guangyu; Chen, Shuaiqi; Xu, Yong; Zhang, Hongtuan (Frontiers in Immunology, 2022)
Background: In reference to previous studies, necroptosis played an important role in cancer development. Our team decided to explore the potential prognostic values of long noncoding RNA (lncRNA) associated with necroptosis in bladder urothelial carcinoma (BLCA) and their relationship in the tumor microenvironment (TME) and the immunotherapeutic response for accurate dosing. Methods: To obtain the required data, bladder urothelial carcinoma transcriptome data were searched from Cancer Genome Atlas (TCGA) (https://portal.gdc.cancer.gov/). We used co-expression analysis and univariate Cox regression to screen out prognostic lncRNA associated with necroptosis. Then the least absolute shrinkage and selection operator (LASSO) was conducted to construct the necroptosis-associated lncRNA model. Based on this model, we also performed the Kaplan–Meier analysis and time-dependent receiver operating characteristics (ROC) to estimate the prognostic power of risk score. Multivariate and univariate Cox regression analysis were performed to build up a nomogram. Principal component analysis (PCA), calibration curves, and time-dependent ROC were also conducted to evaluate the nomogram. In addition, we explored immune analysis, gene set enrichment analyses (GSEA), and evaluation of the half-maximal inhibitory concentration (IC50) in constructed model. Finally, the entire gene set was divided into three clusters based on necroptosis-associated lncRNAs to further compare immunotherapy in cold and hot tumors. Results: A model was built up based on necroptosis-associated lncRNAs. The model revealed good consistence between calibration plots and prognostic prediction. The area of 1-, 3-, and 5-year OS under the ROC curve (AUC) were 0.707, 0.679, and 0.675. Risk groups could be helpful for systemic therapy due to the markedly diverse IC50 between risk groups. To our delight, clusters could effectively identify cold and hot tumors, which would be beneficial to accurate mediation. Clusters 2 and 3 were regarded as the hot tumor, which were more sensitive to immunotherapeutic drugs. Conclusion: The outcomes of our study suggested that necroptosis-associated lncRNAs could effectively predict patients with BLCA prognosis, which may be helpful for distinguishing the cold and hot tumors and improving individual treatment of BLCA.